The Effect of Surfactant on the Stability of Inorganic Salt Hydrated Phase Change Material Containing Graphene Nanoplatelet: An Experimental Investigation - Ahmad Tajuddin, Mohamad; Nor Azwadi, Che Sidik; Norazlianie, Sazali; Wan Mohd Arif, Aziz Japar; Beriache, M'hamed (Akademia Baru, 2024)
The use of nano phase change material (PCM) as a heat transfer agent has spread and expanded as its thermal conductivity is higher than the base PCM, so its use has been increased in PVT systems. In this study, inorganic salt hydrated PCM was used as a base material and Graphene nanoplatelet (GNP) as an additive to improve the thermal conductivity of the resulted nano-PCM and its stability was studied using Cetyl Trimethyl Ammonium Bromide (CTAB) surfactants. The main objective of the present study was to investigate the effect of surfactant on the stability of different GNP concentration in CaCl2.6H2O PCM. The nano-PCM has been prepared using two-step method. The stability of nano-PCM depends on the surfactant used to slow the sedimentation of nanoparticles in the base PCM. The sedimentation process significantly reduces the thermal conductivity of nano-PCM and thus reduces heat transfer. The study results indicated that the employment of surfactant significantly affected the stability of nanoparticles added in the base PCM. The stability test ascertained the effectiveness of the surfactant applied in phase change material. With successive addition of surfactant, the stability of GNP in PCM was further enhanced to +49.3 mV of Zeta potential value.